Chapter Diritto del lavoro e ambiente: ieri e oggi - Pascucci, Paolo (Firenze University Press, 2025)
The essay is inspired by the preface that Riccardo del Punta wrote a few years ago for Paolo Tomassetti's book and, in light of the arguments made by Riccardo on that occasion, focuses on the increasingly current problems relating to the relationship between labour law and the environment on which Riccardo Del Punta himself had carried out interesting and prophetic reflections in an essay years ago, demonstrating in particular a certain disappointment at the lack of attention paid by labour law to environmental issues.